Acute poisoning in children from Jatropha curcas seeds - M C Moshobane; C Wium; L V Mokgola (South African Medical Association, 2017)
The semi-evergreen shrub, Jatropha curcas is native to Central and South America, but now occurs worldwide. Four children suffered severe symptoms of abdominal pain, nausea and vomiting after ingesting the seeds of J. curcas. These cases support the listing of J. curcas as a noxious weed. As a result of this, and a few other incidents, municipal authorities are urged to discourage the use of highly toxic plants such as J. curcas for hedges and garden plants, and to monitor the occurrence of such species. We present a case report about J. curcas poisoning.